2020
DOI: 10.2106/jbjs.19.00804
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Graft Resorption Reduced by the Induced Membrane Technique and Factors Affecting Volumetric Changes

Abstract: Background: Little is known about the volumetric changes of grafted bone over time when using the induced membrane technique. This study investigates the volumetric changes of bone graft using serial computed tomographic (CT) scans following the induced membrane technique. Methods: Patients with critical-sized bone defects had serial CT scans after undergoing bone-grafting using the induced membrane technique. CT scans to evaluate the volume of bone gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Second, uneven bone grafting placement in the membrane may cause resorption of the grafted bone. As a previous study has demonstrated, defects filled with a combination of autograft and demineralized bone matrix (DBM) have a higher incidence of bony resorption than those filled with purely autograft alone [9] . Thus, notching could theoretically occur at defect sites filled with DBM and autograft.…”
Section: Discussionmentioning
confidence: 97%
“…Second, uneven bone grafting placement in the membrane may cause resorption of the grafted bone. As a previous study has demonstrated, defects filled with a combination of autograft and demineralized bone matrix (DBM) have a higher incidence of bony resorption than those filled with purely autograft alone [9] . Thus, notching could theoretically occur at defect sites filled with DBM and autograft.…”
Section: Discussionmentioning
confidence: 97%
“…2). 7 Changes in density of the regenerated bone (1 year after CT) from grafted bone (immediate postoperative CT) were measured by mean Hounsfield unit (HU), which represents attenuation of CT image and correlates with T-score 37 (see Figure, Supplemental Digital Content 1, http://links.lww. com/JOT/B610, which illustrates density measurement of grafted bone and regenerated bone).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Two orthopaedic trauma surgeons used 1 surgical protocol on 143 patients from January 2017 to May 2019 for the management of CSBD due to osteomyelitis, noninfected nonunion, and open fracture. Our surgical protocol was previously described, 7,35,36 and the staged IMT was performed with or without rhBMP-2/HA augmentation (Novosis, CGBIO, Gyeonggi, South Korea) (Fig. 1).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations